Business Plan : Keluarga Jaya Resources (Kerepek KunyaKunya) / Aisyah Harun…[et al.] - Harun, Aisyah; Abu Hassan, Ummi ‘Aqilah; Husni, Nurul Hannani Qistina; Zakaria, Aida Maisarah; Sudin, Nor Afiqah (2021)
This business is based on partnership where it consists of six members, which hold important position in the company such as General Manager, Admin Manager, Finance Manager, Marketing Manager, Operation Manager and Sales Manager. The amount of this business capital is RM26 621, where the total contribution of each member is RM5 325 and the rest is RM74 928 from Bank Islam’s loan. Our company registered as Keluarga Jaya Resources. This company are better known as “Kerepek KunyaKunya” in Kuala Selangor. It operates at Lot 207 Bt 7, Jalan Besar Tanjung Karang. Keluarga Jaya Resources is a company that manufacturing dan distributors of food product that known as “Kerepek”. We are producing variety types of “Kerepek” such as Baulu Kampung, Kerepek Bawang Ayam Hijau, Maruku and many more. ‘Kerepek’ is one of a traditional food that is very popular among the community. It is not only famous during the festive season but also during the normal season. This is because ‘Kerepek’ are suitable to be eaten anywhere. Generally, various ages can eat ‘Chips’ except babies. For many consumers, snacks are for moments of indulgence. The traditional way to boost the experience of indulgence is using innovative flavors. With consumer preferences shifting toward cleaner living lifestyles, artificial flavors are often criticized. So our company decides make sure artificial flavors are being substituted with natural flavors in our ingredient of our snacks, which has resulted in a large variety of natural flavors among the latest product launches. So, with loan given as support from Bank we are sure that our “Kerepek KunyaKunya” able to make our innovation in our snacks becomes real and achieve outstanding demand from customers. Our business is expected commence in march 2021 and our vision is to be the best snack stores that will supplies various of snacks in Malaysia and soon into the global market with a good quality and have our own taste that will satisfies the customers’ satisfaction. We expect that our business will become more developed in the future because with our own recipe that will make sure our customers satisfied with the taste we use in making the snacks, the demand will increase not only festive season only but also during normal season. This will give more advantages for us to make our company get higher profit day by day and will stable in a long run production.